2019
DOI: 10.1108/josm-05-2019-0135
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience in service research: an overview and discussion of its possibilities

Abstract: 2 NEUROSCIENCE IN SERVICE RESEARCH: AN OVERVIEW AND DISCUSSION OF ITS POSSIBILITIES STRUCTURED ABSTRACTPurpose: The paper discusses recent developments in neuroscientific methods and demonstrates its potential for the service field. This work is a call to action for more service researchers to adopt promising and increasingly accessible neuro-tools that allow the service field to benefit from neuroscience theories and insights.Design/methodology/approach: The paper synthesizes key literature from a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 191 publications
(423 reference statements)
0
62
0
7
Order By: Relevance
“…New technologies are opening many possibilities for data fusion from various offline and online sources (Thomadsen et al 2018). Mobile and smart technologies enable the capture and collection of contextual data through myriad sensors and trackers, which enables firms to gain insight into the individual, social, environmental, and market context in a reliable and objective manner (Verhulst et al 2019). The rise of wearable devices offers ample opportunities to collect individual context data such as one’s daily activity rating (i.e., number of steps, calories, sleep hours, pulse rate) and health condition.…”
Section: The Tcq Nomenclature: Methodological Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…New technologies are opening many possibilities for data fusion from various offline and online sources (Thomadsen et al 2018). Mobile and smart technologies enable the capture and collection of contextual data through myriad sensors and trackers, which enables firms to gain insight into the individual, social, environmental, and market context in a reliable and objective manner (Verhulst et al 2019). The rise of wearable devices offers ample opportunities to collect individual context data such as one’s daily activity rating (i.e., number of steps, calories, sleep hours, pulse rate) and health condition.…”
Section: The Tcq Nomenclature: Methodological Challengesmentioning
confidence: 99%
“…People themselves also reveal context-related information through their social media accounts, including likes, shares, posts, and comments that they often grant brands/firms access to through usage of specific apps. Finally, other tools like eye trackers, haptic devices, motion sensors, and microphones allow researchers to develop an understanding of what contextual elements are actually experienced in an objective manner (Verhulst et al 2019). In this area, it may also be helpful to build on insights from environmental and social psychology, behavioral economics, and management literature, which have a tradition of looking at broader contextual influences.…”
Section: The Tcq Nomenclature: Methodological Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…), the proposed/required dimensionality (Gallarza et al 2017; Gallarza, Gil-Saura, and Holbrook 2011) differs. Nevertheless, the importance of conceptualizing CPV along cognitive and emotional dimensions is supported by neuroscience that underlines the predominant role of cognition and emotions in forming individuals’ preferences and perceptions (e.g., Verhulst et al 2019).…”
Section: Positivist View Of Customer Valuementioning
confidence: 99%
“…22 On the other hand, some authors used self-reported daily habits as a measure of RT. 12,25 In addition, diverse issues in the use of survey measures have been identified, 26 as well as matching self-report measures with real-world actions may lead to low-validity conclusions. 27 To overcome these issues, an emerging research field is focusing on how psychocognitive states can be assessed in an ecological, nonintrusive, nonbiased way.…”
Section: Introductionmentioning
confidence: 99%